Journal rankings as a means for structuring bibliographic databases: a case study in Economics and Business Studies - Borst, Timo; Langer, Christian; Schäfers, Susanne (Qualitative and Quantitative Methods in Libraries; Vol 2 No 1 (2013): March 2013 Issue, 2017)
We present an approach towards a web based system of journal rankings for collecting, structuring, maintaining, publishing, retrieving and accessing bibliometric information with a focus on journals in Economics and Business Studies. Providing a gateway to several relevant rankings and journals, we added external information to the individual ranking results including subject categories and information from SHERPA/RoMEO list and the German national Database of Journals (Zeitschriftendatenbank). We outline some possible use cases for journal rankings and give hints on further improvements.